Assessment of actual pulp status using pulp sensibility tests and pulp vascularity tests: A systematic review - Krishnamachari Janani; Kavalipurapu Venkata Teja; Jerry Jose (Wolters Kluwer Medknow Publications, 2022)
Pulp vitality plays an important role in endodontic diagnosis as it has an integral role in primary care. In routine practice, the clinicians rely on pulp sensibility tests. Unfortunately, the major drawback with pulp sensibility tests is that these tests rely on the patient's response to pain and it is subjective in nature. Therefore, the actual status of pulp can be assessed by the vascular response of the tooth. The aim of the systematic review is to evaluate the diagnostic accuracy of pulp sensibility test and pulp vascularity test in identifying the actual status of pulp. The databases of PubMed, Medline, Cochrane Database of Systematic Review, Science Direct, and SCOPUS were searched up to January 2021. Only clinical studies assessing the status of pulp with pulp sensibility test and pulp vascularity test were recruited in this systematic review. The studies considered were based on the data extraction and analysis of the studies for the quality and publication bias. The data collection form was customized. The primary outcome measure was assessing the status of pulp sensibility test and pulp vascularity test. Only clinical study articles were recruited for the systematic review. The search identified 120 articles, out of which 13 duplicate articles and 107 articles were screened. Sixty-seven articles were excluded during the initial screening. Forty full-text articles were retrieved to assess for eligibility. Twenty articles were excluded as it did not fulfil the criteria of the research question. Finally, 20 articles were included for the systematic review. From this systematic review, it can be concluded that pulse oximeter and laser Doppler flowmetry accurately assessed the actual pulp status when compared to pulp sensibility test.